Experimental data on the behavior of a heat-generating fluid in a rotating horizontal cylinder under transverse vibrations - Kozlov, Viktor G.; Vjatkin, Alexei A.; Sabirov, Rustam R. (Data in brief, 2019)
The paper presents experimental data on the effect of transverse vibrations on a heat-generating fluid in a rotating horizontal cylinder. To obtain the data, an original experimental device was designed and manufactured. The data of temperature measurements in the cavity depending on the angular velocity of rotation of the cavity, frequency and amplitude of vibrations are presented. To estimate the intensity and structure of convection, the velocity fields of fluid motion relative to the cavity in cross sections are shown. The paper is related to a research article “Convection of a heat-generating fluid in a rotating cylindrical cavity subject to transverse vibrations” Vjatkin et al, 2019.